(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Acute myocardial infarction (AMI) is the most important form of ischemic heart disease (IHD). Coronary artery disease (CAD) is an increasingly important medical and public health problem and is the leading cause of mortality in Bangladesh. AMI is the rapid development of myocardial necrosis caused by a critical imbalance between the oxygen supply and demand of the myocardium. Total occlusion of the coronary arteries for more than 4-6 hrs results in irreversible myocardial necrosis, but reperfusion within this period can salvage the myocardium and reduce morbidity and mortality. Objectives: To assess the role of carvedilol in prevention of adrenaline induced cardiac damage in experimental animal. Materials and Methods: This experimental study was carried out in the department of pharmacology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka for a period of One year spanning from July 2004 to June 2005. Fifty two healthy rats of Long Evan Norwegian strains, 3-4 months of ages of both sexes, weight between 180-220g were used. The experiment was divided into two parts: Part-I and Part-II. Thirty two rats were selected for Part-I experiment and subdivided into Group-I and Group-II. In Part-II experiment, 20 rats were selected and placed as Group-III. Group-I (12 rats) of control group was treated with 02 doses of inj distilled water (D/W) subcutaneously (S.C.) 24 hrs apart and serum creatine kinase-MB (CK-MB) level and hepatic and cardiac reduced glutathione (GSH) contents were estimated from 06 (Group-Ia) rats after 12 hrs and serum aspartate aminotransferase (AST) level and hepatic and cardiac reduced GSH contents were estimated from 06 (Group-Ib) rats after 24 hrs of 2nd inj of D/W. Group-II (20 rats) was treated with 02 doses of inj adrenaline (2mg/kg) S.C. in 24 hrs interval and in above mentioned way serum CK-MB level, GSH (hepatic and cardiac) contents and serum AST and GSH (hepatic and cardiac) contents were estimated 12 hrs and 24 hrs after the 2nd inj of adrenaline respectively. In experimental group (Group-III) all the rats (20) were treated with carvedilol (1 mg/kg) orally for 14 consecutive days and then were given 02 doses of inj adrenaline with the interval of 24 hrs and again serum CK-MB level and GSH (hepatic and cardiac) contents were estimated from half of the rats (10) after 12 hrs of injection and serum AST level and GSH (hepatic and cardiac) contents were measured from half of the rats (10) after 24 hrs of 2nd injection of adrenaline. Results: Adrenaline (2mg/kg) induced myocardial damage was evaluated biochemically by significant (P˂0.001) increase in CK-MB and AST levels. Free radical production following adrenaline induced myocardial damage was reflected by significant (P˂0.001) depletion in hepatic and cardiac reduced glutathione (GSH) contents. Cardioprotection provided by carvedilol pretreatment in adrenaline induced myocardial infarction was assessed by significant prevention of increase in serum CK-MB and AST levels. Antioxidant property of carvedilol was evaluated by significant (P<0.001) prevention of depletion in hepatic and cardiac GSH contents. The results of the study indicated that carvedilol pretreatment provided effective prevention in adrenaline induced myocardial damage and also provided effective antioxidative action. Conclusion: This study indicated that adrenaline administration induced myocardial damage as evidenced by increase in serum CK-MB and AST levels which was associated with free radical production as reflected by depletion in hepatic and cardiac GSH contents. It was observed that carvedilol through their antioxidant property in addition to their β-blocking effect prevents free radical mediated injury of catecholamine assault following MI. Journal of Armed Forces Medical College Bangladesh Vol.12(2) 2016: 127-134